Increment in Oncovascular Risk Factors and Psychological Distress and Unaltered Vascular Endothelial Function with Advancement of the Stages in Newly Diagnosed Patients with Primary Breast Cancer - Gokul Arora; Zachariah Bobby; Prasanth Ganesan; V. C. Sunitha; Kamila Thalapalliyil (Indian Journal of Medical and Paediatric Oncology)
Background and Aims Oncovascular risk factors are common to both cardiovascular diseases and cancer. Adipocytokines, cell adhesion molecules, and psychological distress may have roles in disease progression.